Türkiye’s migration experience and policy orientations: integrating syrians in higher education - KÜÇÜKCAN, TALİP (My University, 2022)
Türkiye has had multidimensional migration experience not only in its past, but also in its present that has led to the formation of a dynamic migration policy to govern such a dynamic process. Türkiye’s migration policy has been informed and shaped by its geopolitical location as a migrant receiving, labour migrant sending, and migrant transit country. Today, Türkiye hosts the largest number of migrants and refugees in the world with a far-reaching social, political, and economic impact on the country. This article aims to shed light on the multidimensional migration experience of Türkiye and analyse its migration policies to govern manifold challenges brought about by the presence of almost 6 million foreigners in the country. It is argued in this article that the integration of migrants in general and of Syrians in particular remains a major challenge for Türkiye. Therefore, this article recommends that Turkish decision makers should make short and long-term plans for the integration of Syrians as the current conditions indicate that it is unlikely that Syrians will return in any significant numbers any time soon even though the Turkish government has initiated a number of projects in parts of Northern Syria for the safe and voluntary return of its countrymen and women. One important area of integration in this context is higher education, which would enable Syrians to have access to employment and social mobility that would benefi t both themselves and Türkiye.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Siyaset Bilimi; Social Sciences and Humanities; Sociology; Political Science; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; SİYASET BİLİMİ; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; POLITICAL SCIENCE; Siyasi bilimler ve Uluslararası İlişkiler; Genel Sosyal Bilimler; Sosyal Bilimler ve Beşeri Bilimler; Political Science and International Relations; General Social Sciences; Social Sciences & Humanities; Migration; İrregular Migrants; Migration Policy; Türkiye; Syrians in Türkiye; Turkey